FAKTOR YANG MEMENGARUHI BIDAN DALAM KEGIATAN INISIASI MENYUSU DINI DI WILAYAH KERJA PUSKESMAS ONAN HASANG KECAMATAN PAHAE JULU KABUPATEN TAPANULI UTARA TAHUN 2012 - Rutmina Fretti S; Heru Santosa; Asfriyati . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Early initiation of breastfeeding is a natural process of breastfeeding is to provide opportunities for baby to explore and to suck milk itself, within the first hour at the beginning of a baby's life. Early initiation of breastfeeding success of the program is expected to support exclusive breastfeeding. The purpose of this study was to determine the effect of education, training, knowledge, attitudes, actions midwives in Early Initiation of Breastfeeding activities at the the work area Onan Hasang Health Center 2012. This research is a descriptive analytic cross sectional design. The population is all midwives in the work area Onan Hasang Health center 30 people and all were sampled. The data used are primary data obtained through questionnaires and secondary data, in the form of common data and demographic data. Data were analyzed using Chi-Square test. The results showed that the variables that influence the attitude factor (p = 0.034) and action (p = 0.029) with a p-value < α = 0.05. While educational factors (p = 0.586), training factors (p = 0.781), and the knowledge factor (p = 0.272) with a p-value > α = 0.05 in the Early Initiation of Breastfeeding activities. Expected to midwifery education in particular midwives and health workers to improve the quality and service quality in providing midwifery care and applying Early Initiation of Breastfeeding in every birth and provide counseling and education about the Early Initiation of Breastfeeding mothers. Keywords: education, training, knowledge, attitudes, actions, activities IMD